Whole-body positional manipulators for ocular imaging of anaesthetised mice and rats: a do-it-yourself guide - Dietrich, Michael; Cruz-Herranz, Andrés; Yiu, Hao; Aktas, Orhan; Brandt, Alexander U; Hartung, Hans-Peter; Green, Ari; Albrecht, Philipp (BMJ open ophthalmology, 2017)
BackgroundIn vivo retinal imaging of rodents has gained a growing interest in ophthalmology and neurology. The bedding of the animals with the possibility to perform adjustments in order to obtain an ideal camera-to-eye angle is challenging.MethodsWe provide a guide for a cost-effective, do-it-yourself rodent holder for ocular imaging techniques. The set-up was tested and refined in over 2000 optical coherence tomography measurements of mice and rats.ResultsThe recommended material is very affordable, readily available and easily assembled. The holder can be adapted to both mice and rats. A custom-made mouthpiece is provided for the use of inhalant anaesthesia. The holder is highly functional and assures that the rodent’s eye is the centre of rotation for adjustments in both the axial and the transverse planes with a major time benefit over unrestrained positioning of the rodents.ConclusionWe believe this guide is very useful for eye researchers focusing on in vivo retinal imaging in rodents as it significantly reduces examination times for ocular imaging.